2015
DOI: 10.1007/s00018-015-1890-6
|View full text |Cite
|
Sign up to set email alerts
|

F-actin binding protein, anillin, regulates integrity of intercellular junctions in human epithelial cells

Abstract: Tight junctions (TJ) and adherens junctions (AJ) are key morphological features of differentiated epithelial cells that regulate the integrity and permeability of tissue barriers. Structure and remodeling of epithelial junctions depends on their association with the underlying actomyosin cytoskeleton. Anillin is a unique scaffolding protein interacting with different cytoskeletal components, including actin filaments and myosin motors. Its role in the regulation of mammalian epithelial junctions remains unexpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 86 publications
(107 reference statements)
5
37
0
Order By: Relevance
“…Scinderin is an important regulator of F-actin organisation, and F-actin is important in regulating the integrity of intercellular junctions in human epithelial cells, as reported by previous studies [4,15]. In our study, we demonstrated that loss of SCIN decreased the EGFR protein level significantly.…”
Section: Discussionsupporting
confidence: 86%
“…Scinderin is an important regulator of F-actin organisation, and F-actin is important in regulating the integrity of intercellular junctions in human epithelial cells, as reported by previous studies [4,15]. In our study, we demonstrated that loss of SCIN decreased the EGFR protein level significantly.…”
Section: Discussionsupporting
confidence: 86%
“…In mammalian epithelial cells (DU145 and SK-CO15), depletion of Anillin disrupted junctions despite the fact that Anillin localization could not be detected at junctions. Instead, loss of Anillin misregulated junctions through the JNK pathway (Wang et al, 2015) (Figure 4C). …”
Section: Scaffold Proteins Regulate Rho Gtpase Output At Cell-cell Jumentioning
confidence: 99%
“…Therefore mechanisms by which C3 toxin and Anillin siRNA interfere with RhoA are distinct. It was shown that Myosin II activity was not involved in the regulation of intercellular junctions by Anilin in human epithelial (Wang et al, 2015) and we found in osteoclasts that Anillin siRNA does not affect Myosin II activity.…”
Section: Discussionmentioning
confidence: 45%
“…Anillin silencing was also found to increased Jun kinase (JNK) activity in epithelial cells (Wang et al, 2015). JNK is essential downstream of RANK for osteoclast differentiation (Touaitahuata et al, 2014) and also for the formation of podosome rosettes in SrcY527Ftransformed NIH3T3 fibroblasts (Pan et al, 2013), but whether JNK controls osteoclast actin cytoskeleton organization and resorption activity is unknown to date.…”
Section: Discussionmentioning
confidence: 99%